The effects of an eight-week plyometric training program on golf swing performance characteristics in skilled adolescent golfers - Bliss, A.; McCulloch, H.; Maxwell, N. S. (International Journal of Golf Science, 2015)
The purpose of this study was to determine the effects of an eight-week plyometric training intervention on measures of golf swing performance in skilled, adolescent golfers. Sixteen male golfers were recruited to this study, being placed into two handicap and age-matched groups: intervention and control. The intervention group completed an eight-week plyometric training program in addition to their golf-specific practice to study effects on clubhead speed (CHS), ball carry distance (BCD) and other associated measures. The control group continued to undertake their golf-specific training with no plyometric training. The intervention group demonstrated significant (p < 0.05) improvements in CHS and BCD between pre and post trials. The control group showed no significant (p>0.05) changes in golf performance. The results suggest that in skilled adolescent golfers, eight-weeks of plyometric training may help to improve CHS and BCD by approximately 3%. However, large between participant performance differences were observed after the training intervention. It was concluded that, for golfers wishing to improve their CHS and BCD, a golf-specific, plyometric training program could play an important part in the athlete`s training program.